Starch Flocculation by the Sweet Potato Sour Liquid Is Mediated by the Adhesion of Lactic Acid Bacteria to Starch - Zhang, Lili; Yu, Yang; Li, Xinhua; Li, Xiaona; Zhang, Huajiang; Zhang, Zhen; Xu, Yunhe (Frontiers in Microbiology, 2017)
In the current study, we focused on the mechanism underlying starch flocculation by the sweet potato sour liquid. The traditional microbial techniques and 16S rDNA sequencing revealed that Lactobacillus was dominant flocculating microorganism in sour liquid. In total, 86 bacteria, 20 yeasts, and 10 molds were isolated from the sour liquid and only eight Lactobacillus species exhibited flocculating activity. Lactobacillus paracasei subsp. paracasei L1 strain with a high flocculating activity was isolated and identified, and the mechanism of starch flocculation was examined. L. paracasei subsp. paracasei L1 cells formed chain-like structures on starch granules. Consequently, these cells connected the starch granules to one another, leading to formation of large flocs. The results of various treatments of L1 cells indicated that bacterial surface proteins play a role in flocculation and L1 cells adhered to the surface of starch granules via specific surface proteins. These surface starch-binding proteins were extracted using the guanidine hydrochloride method; 10 proteins were identified by mass spectrometry: three of these proteins were glycolytic enzymes; two were identified as the translation elongation factor Tu; one was a cell wall hydrolase; one was a surface antigen; one was lyzozyme M1; one was a glycoside hydrolase; and one was an uncharacterized proteins. This study will paves the way for future industrial application of the L1 isolate in starch processing and food manufacturing.